Prevalence and Prognosis of HFimpEF Developed From Patients With Heart Failure With Reduced Ejection Fraction: Systematic Review and Meta-Analysis - He, Yibo; Ling, Yihang; Guo, Wei; Li, Qiang; Yu, Sijia; Huang, Haozhang; Zhang, Rongting; Gong, Zhiwen; Liu, Jiaxuan; Mo, Liyi; Yi, Shixin; Lai, Disheng; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Heart failure with improved ejection fraction(HFimpEF) is classified as a new type of heart failure, and its prevalence and prognosis are not consistent in previous studies. There is no systematic review and meta-analysis regarding the prevalence and prognosis of the HFimpEF. Method: A systematic search was performed in Medline, Embase and Cochrane Library from inception to 22 May 2021 (PROSPERO registration: CRD42021260422). Studies were included for analysis if the prognosis of mortality or hospitalization were reported in HFimpEF or heart failure with recovered ejection fraction(HFrecEF) patients. The primary outcome was all-cause mortality. Cardiac hospitalization, all-cause hospitalization and composite events of mortality and hospitalization were considered as secondary outcomes. Result: Nine studies consisting of 9491 heart failure patients were eventually included. During an average follow-up of 3.8 years, the pooled prevalence of HFimpEF was 22.64%. HFimpEF had a lower risk of mortality compared with heart failure reduced ejection fraction (HFrEF) (adjusted HR: 0.44, 95% CI: 0.33-0.60). HFimpEF was also associated with lower risk of cardiac hospitalization (HR: 0.40, 95% CI: 0.20-0.82) and composite endpoint of mortality and hospitalization (HR: 0.56, 95% CI: 0.44-0.73). Compared with patients with preserved ejection fraction (HFpEF), HFimpEF was associated with a moderately lower risk of mortality (HR: 0.42, 95% CI: 0.32-0.55) and hospitalization (HR: 0.73, 95% CI: 0.58-0.92). Conclusion: Less than a quarter of HFrEF would be treated to become HFimpEF, who would obtain a two-third decrease in mortality risk. Meanwhile, HFimpEF is associated with lower heart failure hospitalization. Further studies are required to explore how to promote LVEF improvement and improve the prognosis of persistent HFrEF patients.